To solve the simultaneous equations
\[ x = y + 1 \]
\[ x + 2y = 7 \]
we can use the substitution method. Here's a step-by-step solution:
1. Substitute \( x = y + 1 \) into the second equation \( x + 2y = 7 \):
\[ (y + 1) + 2y = 7 \]
2. Simplify the equation:
\[ y + 1 + 2y = 7 \]
\[ 3y + 1 = 7 \]
3. Solve for \( y \):
\[ 3y = 7 - 1 \]
\[ 3y = 6 \]
\[ y = \frac{6}{3} \]
\[ y = 2 \]
4. Substitute \( y = 2 \) back into the first equation \( x = y + 1 \):
\[ x = 2 + 1 \]
\[ x = 3 \]
Therefore, the solution to the simultaneous equations is \( x = 3 \) and \( y = 2 \).
Solve the simultaneous equation x=y+1 and x+2y=7 is
1 answer